Storytelling in scope of public relations' media relations function - (:unkn) unknown (Peter Lang AG, 2017)
Storytelling, one of the most effective means of establishing and persuading an emotional connection with the target groups, is usually used in public relations, which manage communication between the organization and the target groups. An institution's story can be made up of stories told by employees and other target groups as they are created by the organization. Institutions are separated and differentiated from each other by their stories. A public relations practitioner should first create the corporate identity and organization story, and prepare the messages accordingly. This study deals with storytelling techniques in the context of the media relations function of public relations. This study also explores how to create news' value and how to enrich traditional media used in media relations with storytelling techniques, how to attract the interest of media members by using this technique, and so forth. © 2017, Peter Lang GmbH Internationaler Verlag der Wissenschaften Frankfurt am Main. All rights reserved.
Keywords: Media relations; Public relations; Storytelling; Storytelling PR